Inhibitory effect of Ocotea quixos (Lam.) Kosterm. and Piper aduncum L. essential oils from Ecuador on West Nile virus infection. (4th May 2019) - Radice, Matteo; Pietrantoni, Agostina; Guerrini, Alessandra; Tacchini, Massimo; Sacchetti, Gianni; Chiurato, Matteo; Venturi, Giulietta; Fortuna, Claudia
Abstract: West Nile virus (WNV) is a mosquito-borne flavivirus responsible of neuroinvasive manifestations. Natural products are well-known for their biological activities and pharmaceutical application. In this study, the inhibitory effects of essential oils (EOs) of Ocotea quixos (Lam.) Kosterm. and Piper aduncum L. on WNV replication were investigated. WNV was incubated with EOs before adsorption on Vero cells, viral replication was carried out in the absence or presence of EO. Cells were exposed to EO before the adsorption of untreated-virus. GC-MS and GC-FID were used for chemical characterization of EOs. Cell protection from infection was observed for both EOs. P. aduncum EO was characterized by dillapiole as main compound (48.21%) and O. quixos EO by 1, 8-cineole (39.15%). Further investigations, such as the study of molecular and cellular mechanisms of action and in vivo evaluation, should be performed on these essential oils to derive new potential drugs against WNV.